Post-traumatic stress disorder - Grzywa, Anna; Gronkowski, Marek (Current Problems of Psychiatry, 2010)
Post-traumatic stress disorder develops as a delayed and prolonged response to strong short-term or longer-term stressors which act destructively on every person regardless of their resilience Three different factors seem to be relevant: the severity and duration of the stressing event, the personal and emotional characteristics of the victim, and the degree of psychological support received after the trauma. Post-traumatic stress disorder must be differentiated from other mental disorders such as brief psychotic disorder, conversion disorder, major depressive disorder, acute stress disorder, obsessive compulsive disorder, schizophrenia, other psychotic disorders, mood disorder with psychotic features, a delirium, substance-induced disorders, psychotic disorders due to a general medical condition, and malingering.